2015
DOI: 10.4085/1062-6050-49.6.02
|View full text |Cite
|
Sign up to set email alerts
|

Injury History, Sex, and Performance on the Functional Movement Screen and Y Balance Test

Abstract: Context Research is limited regarding the effects of injury or surgery history and sex on the Functional Movement Screen (FMS) and Y Balance Test (YBT). Objective To determine if injury or surgery history or sex affected results on the FMS and YBT. Design Cross-sectional study. Setting Athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 39 publications
8
84
3
4
Order By: Relevance
“…However, the results of the current study suggest that the issues of FMS measurement invariance emerge at the level of individual Copyright ª 2016 National Strength and Conditioning Association A C C E P T E D movement patterns. Interestingly, the movement patterns with poor factor loadings identified in the primary analysis of the current study (i.e., SM, ASLR, TPSU) mirror the movement patterns which consistently demonstrated sex differences in previous literature (1,4,31,33). This finding is consistent with the FMS literature which demonstrates significant sex differences in movement pattern scores yet a lack of sex differences in sum scores (1,4,31,33).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the results of the current study suggest that the issues of FMS measurement invariance emerge at the level of individual Copyright ª 2016 National Strength and Conditioning Association A C C E P T E D movement patterns. Interestingly, the movement patterns with poor factor loadings identified in the primary analysis of the current study (i.e., SM, ASLR, TPSU) mirror the movement patterns which consistently demonstrated sex differences in previous literature (1,4,31,33). This finding is consistent with the FMS literature which demonstrates significant sex differences in movement pattern scores yet a lack of sex differences in sum scores (1,4,31,33).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the movement patterns with poor factor loadings identified in the primary analysis of the current study (i.e., SM, ASLR, TPSU) mirror the movement patterns which consistently demonstrated sex differences in previous literature (1,4,31,33). This finding is consistent with the FMS literature which demonstrates significant sex differences in movement pattern scores yet a lack of sex differences in sum scores (1,4,31,33). The measurement invariance findings of the current study are also consistent with recent FMS research which suggests that the FMS demonstrated moderate levels of accuracy in predicting female Coast Guard cadets' injury risk and low accuracy in predicting male cadets' injury risk (25).…”
Section: Discussionsupporting
confidence: 66%
“…There was no significant difference between these groups in the aggregate FMS score; however female athletes reached further than general college students in all directions in the YBT [13]. Another study administered the FMS and the YBT in 200 NCAA Division I athletes and found that individuals with a self-reported history of injury or surgery had significantly lower aggregate FMS scores [14]. They also reported that female athletes had lower scores on some of the individual tests within the FMS (TSPU and RS) and higher scores on other tests (ILL, SM, and ASLR [14]).…”
Section: Introductionmentioning
confidence: 99%
“…Another study administered the FMS and the YBT in 200 NCAA Division I athletes and found that individuals with a self-reported history of injury or surgery had significantly lower aggregate FMS scores [14]. They also reported that female athletes had lower scores on some of the individual tests within the FMS (TSPU and RS) and higher scores on other tests (ILL, SM, and ASLR [14]). However, they did not observe statistically significant differences in the YBT reach distances between individuals with and without a self-reported history of injury or surgery, nor between male and female participants [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation